PEMAHAMAN DISPENSASI PERKAWINAN DIBAWAH UMUR DI DESA SERDANG MELALUI PRORAM PKK PEDULI PEREMPUAN - Rafiqa Sari; Yokotani; Darwance; Muhammad Syaiful Anwar; A.Cery Kurnia (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract In the Marriage Law in Indonesia, it is stated that one of the marriages is that a man and a woman who will become prospective husband and wife have matured and are physically and mentally ready to carry out the marriage, from this it can be concluded that mental, physical, and strong determination are needed to prepare for marriage. continue to live with a partner. The Province of the Bangka Belitung Islands is included in one of the provinces in Indonesia where the number of underage marriages is quite high. This is a separate legal problem for the lives of couples who carry out underage marriages. Due to this condition, the authors are interested in conducting community service with one of the existing problems, which is related to the importance of understanding the underage dispensation for the community in Serdang Village through the PKK Peduli Perempuan program. This paper aims to provide an understanding of the community regarding the dispensation of underage marriage, the method of implementing the service used is through counseling and socialization. The results based on the knowledge of understanding the dispensation of underage marriages are very important to be known by the public. Abstrak Dalam Undang-Undang Perkawinan di Indonesia menyebutkan salah satu asas perkawinan adalah laki-laki dan perempuan yang akan menjadi calon suami istri telah matang jiwa maupun raganya agar dapat melangsungkan perkawinan, dari hal tersebut dapat dipahami bahwa sangat dibutuhkan kesiapan mental, fisik, maupun tekad yang kuat untuk terus hidup bersama pasangan. Provinsi Kepualaun Bangka Belitung, masuk dalam salah satu provinsi di Indonesia yang angkat perkawinan dibawah umur cukup tinggi. Hal ini menjadi permasalahan hukum tersendiri bagi kelangsungan hidup pasangan yang melangsungkan perkawinan dibawah umur. Atas kondisi ini, maka penulis tertarik menyelenggarakan pengabdian kepada msyarakat dengan salah satu permasalahan yang ada, yaitu terkait pentingnya pemahaman dispensasi dibawah umur bagi masyarakat di Desa Serdang melalui program PKK Peduli Perempuan. Tulisan ini bertujuan memberikan pemahaman terhadap masyarakat terkait dispensasi perkawinan dibawah umur, metode pelaksanaan pengabdiaan yang digunakan adalah melalui penyuluhan dan sosialisasi. Berdasarkan hasil penelitian diketahui pemahaman dispensasi perkawinan dibawah umur sangat penting diketahui oleh masyarakat